Can Migration Reduce Educational Attainments? Depressing Evidence from Mexico - David McKenzie; Hillel Rapoport (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2006)
This paper examines the impact of migration on educational attainments in rural Mexico. Using historical migration rates by state to instrument for current migration, we find evidence of a significant negative effect of migration on schooling attendance and attainments of 12 to 18 year-old boys and of 16 to 18 year-old girls. IV-Censored Ordered Probit results show that living in a migrant household lowers the chances of boys completing junior high-school and of boys and girls completing high-school. The negative effect of migration on schooling is somewhat mitigated for younger girls with low educated mothers, which is consistent with remittances relaxing credit constraints on education investment for the very poor. However, for the majority of rural Mexican children, family migration depresses educational attainment. Comparison of the marginal effects of migration on school attendance and on participation to other activities shows that the observed decrease in schooling of 16 to 18 year olds is accounted for by current migration of boys and increases in housework for girls.
Keywords: O15; J61; D31; 330; Migration; migrant networks; education attainments; Mexico